Entirely intracanalicular meningioma: contrast-enhanced MR findings in a rare entity. - Haught, K; Hogg, J P; Killeffer, J A; Voelker, J L; Schochet, S S (American Journal of Neuroradiology, 1998)
We report an unusual case of an entirely intracanalicular meningioma in a 51-year-old woman. Contrast-enhanced MR images showed an enhancing lesion filling the lateral portion of the left internal auditory canal. Our findings suggest that meningiomas should be considered in the differential diagnosis of entirely intracanalicular masses.